THE EFFECT OF WORK MOTIVATION, WORK EXPERIENCE, AND WORK TRAINING ON EMPLOYEE PERFORMANCE AT THE PAKRAMAN PEGUYANGAN VILLAGE LPD IN DENPASAR - I Putu Deva Aditya Putra; Pande Ketut Ribek; Tiksnayana Vipraprastha (Lembaga Penelitian dan `Pengabdian Kepada Masyarakat (LPPM), 2025)
This study aims to determine the effect of work motivation, work experience, and job training on employee performance at the Village Credit Institution (LPD) of Pakraman Peguyangan Village, North Denpasar, Denpasar City. The population in this study consisted of all 37 employees, and all members of the population were used as respondents, thus sampling was conducted using the census method. The collected data were analyzed using multiple linear regression, correlation, determination, F-test, and t-test. The results of the analysis show that: 1) Work motivation has a positive and significant effect on employee performance at the Village Credit Institution (LPD) of Pakraman Peguyangan Village, North Denpasar, Denpasar City. 2) Work experience has a positive and significant effect on employee performance at the Village Credit Institution (LPD) of Pakraman Peguyangan Village, North Denpasar, Denpasar City. 3) Job training has a positive and significant effect on employee performance at the Village Credit Institution (LPD) of Pakraman Peguyangan Village, North Denpasar, Denpasar City.